Digital puzzle: Alternative media for cell learning in middle school - Munawarah Fauziah Fazrianti Yulinda; Much. Fuad Saifuddin (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Digital-based biology learning media is very suitable for learning in the era of globalization, especially in visualizing abstract material. Students are familiar with puzzle games; variations of digital puzzles are required for visualization cell materials. This research focuses on developing and finding learning media in the form of digital cell puzzles to use them to understand learning material that is not boring. The digital puzzle learning media developing with a 4-D development model (Define, Design, Develop and Disseminate). The developed digital puzzle learning media got value highly for using in learning cell material with assessments from material experts 81.72%, media experts 89.10%, teachers 97.82%. Student responses on the small-scale test (91.90%) and the large-scale test (93.53%) in the criteria are very good or very useful for learning. Digital-based learning such as digital puzzles can be interesting learning in the era of globalization.Abstrak Media pembelajaran biologi berbasis digital sangat cocok digunakan untuk pembelajaran di era globalisasi terutama dalam memvisualisasikan materi yang abstrak. Siswa akrab dengan permainan puzzle; variasi teka-teki digital diperlukan untuk visualisasi bahan sel. Penelitian ini berfokus pada pengembangan dan penemuan media pembelajaran berupa digital cell puzzles untuk digunakan dalam memahami materi pembelajaran agar tidak membosankan. Media pembelajaran puzzle digital dikembangkan dengan model pengembangan 4-D (Define, Design, Develop, dan Disseminate). Media pembelajaran puzzle digital yang dikembangkan mendapat nilai tinggi untuk digunakan dalam pembelajaran materi sel dengan penilaian ahli materi 81,72%, ahli media 89,10%, guru 97,82%. Respon siswa pada tes skala kecil (91,90%) dan tes skala besar (93,53%) dalam kriteria sangat baik atau sangat bermanfaat untuk pembelajaran. Pembelajaran berbasis digital seperti media puzzle digital ini dapat menjadi pembelajaran yang diminati di era globalisasi.